2021
DOI: 10.1002/ps.6681
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced and sustainable control of Myzus persicae by repellent plants in organic pepper and eggplant greenhouses

Abstract: BACKGROUND: Repellent plants (RPs), generally used to keep pests away from crops in integrated pest management, have been shown to reduce the need for synthetic insecticide sprays in various agroecosystems. However, few studies have evaluated the pest control efficiency of RPs over the entire growth period of crops. To evaluate the effect of RPs against Myzus persicae and explore the application and management modes of RPs in the field, we planted mint (Mentha haplocalyx), mung bean (Vigna radiata), celery (Ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…A mixture of nonanal and (Z)-3-hexen-1-ol can significantly attract the syrphid fly Paragus quadrifasciatus Meigen (Diptera: Syrphidae) in the field ( Yu et al., 2008 ), and the mixture of α-terpineole and 1,8-cineole repelled the fall armyworm Spodoptera frugiperda J. E. Smith (Lepidoptera: Noctuidae) ( Lima et al., 2009 ). In recent years, a growing body of literature has shown that volatiles of plant can attract natural enemies or/and repel pests in pest management programs ( Yao et al., 2021 ; Wang et al., 2022 ). That is, it is strategic to study the active substances that have attractive effects on H. axyridis and explore their mixed ratios for conservation biological control.…”
Section: Discussionmentioning
confidence: 99%
“…A mixture of nonanal and (Z)-3-hexen-1-ol can significantly attract the syrphid fly Paragus quadrifasciatus Meigen (Diptera: Syrphidae) in the field ( Yu et al., 2008 ), and the mixture of α-terpineole and 1,8-cineole repelled the fall armyworm Spodoptera frugiperda J. E. Smith (Lepidoptera: Noctuidae) ( Lima et al., 2009 ). In recent years, a growing body of literature has shown that volatiles of plant can attract natural enemies or/and repel pests in pest management programs ( Yao et al., 2021 ; Wang et al., 2022 ). That is, it is strategic to study the active substances that have attractive effects on H. axyridis and explore their mixed ratios for conservation biological control.…”
Section: Discussionmentioning
confidence: 99%
“…63 Such volatile and/or visual cues potentially also explain the reduced aphid infestation levels in eggplant intercropped with mung bean, mint, celery or coriander. 64 Meanwhile, companion plants often provide shelter and (food) resources to foraging natural enemies, 65 as observed when interplanting alyssum in broccoli. 66 The earlier processes routinely occur in sync: volatiles from molasses grass for example repel stemborers and concurrently attract parasitoids in cereal grains.…”
Section: Discussionmentioning
confidence: 99%
“…In the process of crop production, we can cultivate functional plants in advance and select their best application period, including the vegetative and flowering stages, which can be applied during the whole crop production cycle. By selecting functional plants that also benefit natural enemies during their vegetative stages or that repel target pests [ 45 ], one can extend their contribution to non-chemical pest management. Overall, these synergisms should be actively pursued in order to maximize the potential of functional plants in biological control.…”
Section: Discussionmentioning
confidence: 99%